Hydrogenolysis of Propane over Sol-Gel Pt-Rh/SiO2: Activity, Selectivity and Kinetics - S. MAHMOUD, SABRI (Asian Journal of Chemistry, 2010)
The catalytic properties of PtxRh1 _ x (x = 0, 0.2, 0.4, 0.5, 0.6, 0.8, 1.0) bimetallic catalysts supported on SiO2 and prepared by the sol-gel method have been investigated in the hydrogenolysis of propane in the temperature range of 150-550oC. The measured BET surface area of these catalysts is relatively high (ca. 580 m2/g). Their temperature of 100% conversion of propane to ethane and methane at H2/C3H8 = 3 and space velocity of 12,000 h -1 is relatively low (200-270°C). All Pt-Rh/SiO2 catalysts are very active in this respect. whereas Pt/SlO2 is relatively inactive. Their selectivity towards the production of ethane is ca. 50%. The kinetic parameters for this reaction over Pt50Rh50/SiO2 are also reported, where increasing the hydrogen pressure has an adverse effect on the rate of this conversion. The reaction order with respect to hydrogen pressure is strongly negative (-2). Propane pressure has a slight effect on the rate of conversion, and is with an observed reaction order of +0.55. The apparent activation energy was determined and found to be 123 ± 7 kJ/mot.